How they voted a guide to how your congressmen voted on bills passed in Congress (July 1989-June 1990). (Makati Makati Business Club and NAMFREL-Bantay ng Bayan Foundation, 1992)
"The Congressional report contains the complete vote record and directory of bills passed by the House of Representatives and the Senate. For this edition, the legislative record and performance of the House as of the third regular session (July 1989 to June 1990) is presented." It is also a compilation of voting records of all Bills passed on final reading by the Senate and House of Representatives. It contains articles on the legislative and attendance records and a description of the legislative process. It also includes House Performance Review, some facts about our Congressmen, The Legislative Process: how a bill became a law; a closer look at lawmaking and list of house expenditures." Includes an index.
Title from cover.
Keywords: Parliamentary practice -- Philippines; Legislators -- Performance. -- Philippines